2018
DOI: 10.1016/j.triboint.2018.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Observations of dry particles behaviour at the tyre/road interface

Abstract: Previous studies highlighted that friction value measured on real road surface textures covered by particles depends on particle sizes. This paper focuses on identification of particles behaviours at the tyre/road interface in the presence of particles. Identification is made by visual observations through high-speed camera, focus-variation microscopy and Scanning Electron Microscopy on the contaminated surface as scratch analysis on the surface. Two particle types were collected into samples picked next to ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 18 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…With fractions 50-80µm and 80-100µm, the cloud of particles is less dense. After Changarnier and coauthors [17], as quartz (predominant element in the composition of the particles) and aluminum are harder than rubber, the slider is the most deformed in the interaction slider / particles / substrate. Just as the particles leave the interface between the slider and the substrate, the slider recovers its initial geometry and there is a pinching effect that throws the particles up a few millimeters behind the slider; once in the air, the particles either settle on the substrate or are entrained by the air flow and leave the substrate.…”
Section: Close-up Viewsmentioning
confidence: 97%
See 3 more Smart Citations
“…With fractions 50-80µm and 80-100µm, the cloud of particles is less dense. After Changarnier and coauthors [17], as quartz (predominant element in the composition of the particles) and aluminum are harder than rubber, the slider is the most deformed in the interaction slider / particles / substrate. Just as the particles leave the interface between the slider and the substrate, the slider recovers its initial geometry and there is a pinching effect that throws the particles up a few millimeters behind the slider; once in the air, the particles either settle on the substrate or are entrained by the air flow and leave the substrate.…”
Section: Close-up Viewsmentioning
confidence: 97%
“…Chemical analysis (detailed in [17]) shows that the particles are mainly composed of Si (68%) which is a hard mineral. The other elements are: Na (3.5%), K (4%) and Mg (1.5%) whose presence can be explained by industrial sites located next to the Cheviré bridge; metallic components such as Al (12%) and Fe (6%) whose presence can be attributed to the wear of braking system and tires; and other elements in insignificant amounts [17]. It was shown in [2] that the chemical composition of the particles extracted from sediments is similar to that of particles collected directly from the road surface.…”
Section: Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…8 In addition, depending on the size and type of particles, the characteristics and the rheological behaviour of these sand films and friction mechanisms like rolling, scratching and crushing were observed. 12 Besides, some research works have identified the factors affecting friction coefficient which are young ice or old ice, film water layer, ice temperature, sand grain size, grain morphology, grain distribution, etc.…”
Section: Introductionmentioning
confidence: 99%